Digital Growth Mindset as a Catalyst for Team Collaboration and Communication Skills in Higher Education - Afriska Yuni Anggraini; A. Sobandi; Selvi Permata Groda (Jurnal Inovasi Pendidikan Ekonomi, 2025)
This study aims to analyze the influence of Digital Growth Mindset (DGM), Digital Communication Skills (DCS), and Team Collaboration Skills (TCS) among Indonesian student’s, to assess how a digital growth mindset affects these crucial competencies in the digital age. The population of this study is all students in Indonesia, particularly in East Java and Central Java. The sampling technique used is purposive sampling. The sample size in this study is 214 respondents. The primary data was collected through an online questionnaire distributed via Google Forms. The quantitative data analysis technique used the Partial Least Squares (PLS-SEM) method. The study results show that DGM significantly enhances DCS and TCS, with moderate explanatory power. While other factors, such as prior digital experience, may contribute, the findings emphasize cultivating a growth-oriented mindset among students. The novel contribution of this study is exploring the role of DGM in the context of digital education in Indonesia, which is still limited in the literature, and demonstrating how a growth-oriented mindset can influence the skills that are highly needed in the digital era. This study opens opportunities for developing adaptive curricula to address digital challenges and encourages further research on factors influencing digital competencies in education